Motives and Perceptions of Cannabis Use among a Sample of Employed Graduates in Malaysia: A Qualitative Study - Neshalatha Govarthnapany; Darshan Singh; Suresh Narayanan; Balasingam Vicknasingam (Elsevier, 2021)
Objective: Cannabis use is criminalized in Malaysia under existing drug laws, despite the prevailing contrasting views towards cannabis regulation. We sought to determine the motives for using cannabis, perceptions regarding the risks of using it, and the legal ramifications related to its use among employed graduates in Malaysia. Design: Twenty-three employed graduates were recruited through snow-ball sampling for this qualitative study. The interviews were recorded, transcribed verbatim and analyzed based on the respondents' testimonies. Results: The majority were females (52%, n=12/23), and Malay (57%, n=13/23). Nearly 87% (n=20/23) were single (including one divorcee). The respondents' mean age was 30.9 years (SD=5.2), and the mean age at which cannabis was first used was 20.5 years (SD=3.1). The majority used cannabis for recreational (60%, n=16/23), and medicinal (30%) purposes. Cannabis use was associated with perceived positive effects and the belief that it is a safe substance. It was also regarded to be safer than conventional pharmacotherapy in treating self-disclosed psychological symptoms. The few who wanted but had difficulty abstaining from cannabis use avoided seeking treatment due to the fear of prejudice from treatment providers. Users also felt that drug laws are being applied unevenly to favour the well-connected. In general, users want a more liberalized approach to cannabis use. Conclusions: The use of cannabis among educated, employed individuals persists because they remain functional and appear to be unharmed by extended use. They are either unconcerned or unaware of the negative side of cannabis use. Making them aware of the negatives in an intelligent and fact-based manner will help them make informed decisions.